Identity of Salvia weihaiensis (Lamiaceae) from China - Hu, Guo-Xiong; Peng, Hua (Phytotaxa, 2015)
Salvia Linnaeus (1753: 23) (tribe Mentheae, subfamily Nepetoideae) is by far the largest genus of Lamiaceae with approximately 1000 species (Alziar 1988–1993). Molecular phylogeny researches demonstrate that the genus is polyphyletic, and the clade “Salvia” in effect includes four distinct lineages, with intercalation of five other genera of tribe Mentheae (Walker et al. 2004, Walker & Sytsma 2007, Takano & Okada 2011, Will & Claßen-Bockhoff 2014). East Asia is one of three centers of diversity of Salvia with approximately 100 species (Walker et al. 2004), 82 species are native to China (Li & Hedge 1994, Hu et al. 2014). Additionally, S. coccinea Buc’hoz ex Etlinger (1777: 23) and S. tiliifolia Vahl (1794: 3), which are native to Central and South America, have naturalized successfully in China (Li & Hedge 1994, Hu et al. 2013).